High prevalence of plastic ingestion by Eriocheir sinensis and Carcinus maenas (Crustacea: Decapoda: Brachyura) in the Thames Estuary. (October 2020) - McGoran, Alexandra R.; Clark, Paul F.; Smith, Brian D.; Morritt, David
Abstract: This study presents evidence for microplastic contamination in two resident species of brachyuran crab from the Thames Estuary: the native shore crab, Carcinus maenas (Linneaus, 1758) and the invasive Chinese mitten crab, Eriocheir sinensis (H. Milne Edwards, 1853). The gills, gastric mill and intestine of 94 C. maenas and 41 E. sinensis were examined. Crabs were sampled periodically (ca. every three months) between December 2018 and October 2019. A total of 874 plastics were recovered, ranging 34 μm–34 mm in length. Overall, 71.3% and 100% of C. maenas and E. sinensis, respectively, contained at least one item (fibre, film, fragment or tangle of fibres) in the gill chamber, gastric mill or gastrointestinal tract. The most common items were fibres (78.5%) but in some cases, particularly in the gastric mill, these were aggregated into tangles (7.8%). Almost all E. sinensis contained tangles of fibres (95.1%), whereas, relatively few C. maenas contained similar tangles (10.6%). Graphical abstract: Image 1 Highlights: Thames Estuary crabs, Carcinus maenas and Eriocheir sinensis, ingest microplastic. Fibres were the most dominant form recovered (detection limit was 32 μm in length). Tangles of fibres, many comprising >100 items, had accumulated in the gastric mill. Tangles were too large to pass beyond the gastric mill and may be retained. Balloon, sanitary pad, carrier bag and elastic band fragments were also ingested. Abstract : This study presents a comparison of microplastic load in two species of brachyuran crab in the Thames Estuary, over 70% of sampled individuals were contaminated.